Characterization of the diversity of pollinating insects and their interactions with the flora of the “Agro-forêts pour le développement de Kipushi” perimeter - Makolo Kasongo, Pierre; Tshibungu Nkulu, Alain; Ngoy Shutcha, Mylor; Bugeme, David Mugisho (Frontiers in Bee Science, 2025)
Anthropogenic disturbances mainly involve the loss of habitats in tropical regions where there is also significant population growth. These disturbances also have an impact on the plant pollination service, which is struggling to be explored in the Lubumbashi region, where mining interests seem to take priority given the local connotations and the predominance of players within the sector. The present study focuses on an analysis of the pollination service and the interactions maintained between bees and their host plants, in a context of agricultural impetus through the practice of agroforestry, the benefits of which supposedly extend from improved yields to efforts to conserve global biodiversity. Subject to the sampling effort at the limits of the favorable periods, our results indicate a significant biodiversity of bees, unevenly distributed among the families Apidae, Halictidae and Megachilidae. The species Xylocopa albiceps, Nomia speciosana, X. olivaceae and Megachile torrida dominate the abundance ranks, while more restricted than general interactions between pollinators and their host plants are recorded.